The spirit is willing - Baker, Betty (New York : Macmillan Publishing Company, 1974)
Carrie's boredom disappears when she and her friend decide to hold a séance in their Arizona mining town one summer in the 1880's.
1. Apache Sam's skedaddle -- 2. Greasy Dan's sale -- 3. Miss brewster's talking -- 4. The spirit 's scare -- 5. Portias's grand swoon -- 6. The mummy's move -- 7. "What's this I hear? -- 8. Frank ainsley's test -- 9. Chickalimmy's voice -- 10. Carrie's million and one.
Keywords: SOCIAL LIFE AND CUSTOMS -- FICTION